Let's simplify step-by-step.<span><span><span>12+<span><span>8x</span><span>(<span>4+3</span>)</span></span></span>+2</span>−6</span><span>=<span><span><span><span>12+<span>56x</span></span>+2</span>+</span>−6
</span></span>Combine Like Terms:<span>=<span><span><span>12+<span>56x</span></span>+2</span>+<span>−6</span></span></span><span>=<span><span>(<span>56x</span>)</span>+<span>(<span><span>12+2</span>+<span>−6</span></span>)</span></span></span><span>=<span><span>56x</span>+8
</span></span>Answer:<span>=<span><span>56x</span>+<span>8
Good luck mate :P</span></span></span>
Answer:
6 1/5
Step-by-step explanation:
Answer:
15,300 + 18750 + 13,500 + 23,400 +19500 = 90,450
Step-by-step explanation:
divide all the numbers by 100, then multiplying by 3
Answer:
Yuhh the answers c dawhggg trus me i just did the same thing lawl!
Step-by-step explanation:
Answer: 17/20=0.85
Step-by-step explanation: